THE EFFECT OF COOPERATIVE LEARNING MODEL TYPE TEAMS GAMES TOURNAMENT (TGT) ON THE MATERIAL SUBSTANCE AND CHANGES TO THE LEARNING OUTCOMES OF STUDENTS IN GRADE VII JUNIOR HIGH SCHOOL - Sari, Ayu Puspita; Zahra, Firda Az; Oktavia, Rani; Azhar, Aulia (Universe, 2025)
Cooperative learning model type Teams Games Tournament (TGT) is one of the learning models that involve all student activities, peer tutors between students, containing games that can create fun learning. By applying the TGT model, students will be more motivated to learn and will be able to improve student learning outcomes. The purpose of this study was to see the effect of cooperative learning model type Teams Games Tournament (TGT) on the material substance and changes to the learning outcomes of students in grade VII junior high school. This study is included in the type of Quasi-experimental research using a research design that is Nonequivalent Control Group Design. The sampling technique used is Purposive Sampling. The sample consisted of one experimental class using cooperative model type TGT and one control class using lecture and discussion method. The instrument used is a written test with multiple choice questions. This study conducted statistical analysis with the help of Microsoft Excel. Based on the hypothesis test with the test U (Mann Whitney) diperolehkan zhitung value of 3.01 and ztabel of 1.96. Seen H1 accepted, so it can be concluded that the cooperative learning model type TGT has a significant influence on the learning outcomes of students in grade VII Junior High School on the material substance and its changes.